(3GdEjVGM aj TQM ebGeGJ GdMQjQjs - (3fGUQ Hf YHO GdSjO CHj GdecGQe GHf Ydj, CHh GdaJM, HQgGf GdOjf GdNhGQRej GdeWQRj , J (B610 (3g`s; (3GdMQjQj,J (B516 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje Gddge , cdeI JSJYed ai GdOYGA HeYfi jG Gddg hGdeje ajgG YhV Yf MQa GdfOGA hdPdc dGjLeY HjfgeG, hEfeG aJMJ ef bHd Cf GdMQha eHfjI s
(3BNQgG (B:s
(3acd ef SeY HGSeg , hXaQ HhSeg , hVYg Ydi beI GdQhGL , hJbHdg HbHhd MSf heG GfS CfS ehdGi GdUOQ GdcHjQ GdYdGeI Sbi Gddg GdMQjQi TBHjH QVhGfg, hcSGg LdGHjH ZaQGfg s
(3JfbU ef ChdgG GdNWHI hJbY ai (B21 (3hQbI ai fSNI SHgSdGQs
(3fSNI SGOSIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B108s
Keywords: (3GdCOHs